Through Their Eyes: Contextualized Analysis of Drawings by Former ISIS Child Soldiers in Iraq - Aisha-Nusrat Ahmad; Phil C. Langer (Social Inclusion)
This article presents a contextualized interpretation of drawings created by former child soldiers of the so‐called Islamic State in Iraq and Syria (ISIS). The drawings were generated as part of a collaborative storytelling project in Northern Iraq in 2019 that aimed at identifying the psychosocial needs of these militarized children. The analysis focuses on two distinct groups: Arab‐Sunni and Yezidi boys, each representing different pathways into and experiences within ISIS, leading to varied forms of social stigmatization. The findings reveal significant differences in how violence, agency, and social attributions are represented in the narratives and drawings of the two groups. The study underscores the importance of collaborative meaning‐making in representing marginalized groups and highlights the potential to combine drawings with other qualitative methods to minimize the risk of over‐interpretation. This approach provides nuanced insights into the children’s struggle for agency and interpretative ownership in the face of powerful social narratives. This article contributes to the broader discourse on child soldiers and the use of visual methodologies in conflict‐affected areas.